2020
DOI: 10.1371/journal.pgen.1009035
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylome of human sperm is distinct from blood with little evidence for tissue-consistent obesity associations

Abstract: Epidemiological research suggests that paternal obesity may increase the risk of fathering small for gestational age offspring. Studies in non-human mammals indicate that such associations could be mediated by DNA methylation changes in spermatozoa that influence offspring development in utero. Human obesity is associated with differential DNA methylation in peripheral blood. It is unclear, however, whether this differential DNA methylation is reflected in spermatozoa. We profiled genome-wide DNA methylation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
(104 reference statements)
3
11
0
Order By: Relevance
“…While most probes mapped to open seas in liver (1014 probes), nasal (1100), adipose (1280) and sperm (1063), greater fractions of open sea probes mapped to genes in liver (70% of open sea probes), nasal (74%) and adipose (71%) than in sperm (52%, Figure 4C ). This observed sparsity of CpG island regions and enrichment of open sea, intergenic and gene body regions among CpG probes with tissue-specific DNAm was recently corroborated in an independent study comparing DNAm in matched sperm and blood samples directly ( 30 ). This corroboration was especially striking because the discovery set samples in ( 30 ) were processed on the newer EPIC/HM850K rather than the HM450K platform.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…While most probes mapped to open seas in liver (1014 probes), nasal (1100), adipose (1280) and sperm (1063), greater fractions of open sea probes mapped to genes in liver (70% of open sea probes), nasal (74%) and adipose (71%) than in sperm (52%, Figure 4C ). This observed sparsity of CpG island regions and enrichment of open sea, intergenic and gene body regions among CpG probes with tissue-specific DNAm was recently corroborated in an independent study comparing DNAm in matched sperm and blood samples directly ( 30 ). This corroboration was especially striking because the discovery set samples in ( 30 ) were processed on the newer EPIC/HM850K rather than the HM450K platform.…”
Section: Resultssupporting
confidence: 53%
“…This observed sparsity of CpG island regions and enrichment of open sea, intergenic and gene body regions among CpG probes with tissue-specific DNAm was recently corroborated in an independent study comparing DNAm in matched sperm and blood samples directly ( 30 ). This corroboration was especially striking because the discovery set samples in ( 30 ) were processed on the newer EPIC/HM850K rather than the HM450K platform.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Similarly, one investigation indicated that parental diet can modulate the methylation levels of several genes, including liver-specific genes involved in cholesterol/lipid metabolism, whereas no effect of paternal diet on sperm DNA methylation was found in other studies (Carone et al, 2010;Rando and Simmons, 2015;Shea et al, 2015;Whitelaw, 2015). Similarly, parental pre-conceptional obesity could potentially impact on the establishment of imprinting marks during embryogenesis (Soubry et al, 2015;Ou et al, 2019;Åsenius et al, 2020b;Keyhan et al, 2021). Changes in methylation in two imprinted genes, PLAGL1 and MEG3, have been detected in umbilical cord blood leukocytes in a group of newborns from obese mothers, making a link between maternal overnutrition and the impairment of imprinting marks in the offspring (Soubry et al, 2015).…”
Section: Lifestyle Factorsmentioning
confidence: 99%